1925
DOI: 10.1084/jem.42.3.347
|View full text |Cite
|
Sign up to set email alerts
|

Immunological Reactions of the Isolated Carbohydrate and Protein of Pneumococcus

Abstract: In a previous paper on the immunological relationships of the cell constituents of Pneumococcus (1) two chemically distinct substances, namely the carbohydrate and protein of the cell, were shown to be intimately concerned in the serological specificity of this organism.The facts recorded at that time related only to the reactions exhibited by these substances in antipneumococcus serum prepared by immunization with the whole bacterial cell. In the absence of final evidence as to the antigenic properties of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

1926
1926
1983
1983

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(9 citation statements)
references
References 2 publications
0
9
0
Order By: Relevance
“…Experiments are in progress to determine the identity of the protective immunogen(s) in the pneumococcal vaccine. Pneumococcal antigens already described in the literature, which could possibly be the active substance in the PSP-3R vaccine, are C-polysaccharide (24), F-polysaccharide (8, 15), the "nucleoprotein" antigen (3)(4)(5)(6), lipoteichoic acids (7,25), and the uncharacterized R antigen (12,14). However, even if the immunogen proves to be one of these, its presence cannot accoupt completely for the immunogenicity of PSP-3R, since the immunogenicity of the vaccine is sensitive to treatment with ribonuclease (21).…”
Section: Yl Imentioning
confidence: 99%
“…Experiments are in progress to determine the identity of the protective immunogen(s) in the pneumococcal vaccine. Pneumococcal antigens already described in the literature, which could possibly be the active substance in the PSP-3R vaccine, are C-polysaccharide (24), F-polysaccharide (8, 15), the "nucleoprotein" antigen (3)(4)(5)(6), lipoteichoic acids (7,25), and the uncharacterized R antigen (12,14). However, even if the immunogen proves to be one of these, its presence cannot accoupt completely for the immunogenicity of PSP-3R, since the immunogenicity of the vaccine is sensitive to treatment with ribonuclease (21).…”
Section: Yl Imentioning
confidence: 99%
“…Freund and Bonanto (22) in 1944 had incorporated pneumococcal polysaccharide (type not stated) in adjuvant containing mycobacteria in efforts to induce antibodies or hypersensitivity in rabbits. Their failure may have reflected the relative inability of this species to respond immunologically to such polysaccharides (23)(24)(25). Failure with type III pneumococcal polysaccharide in guinea pigs was reported by Maurer and Mansmann (26) with small inducing doses (10 ttg) which could have been an insufficient quantity for sensitization.…”
mentioning
confidence: 93%
“…Tillett showed that immunizing rabbits with a rough pneumococcal strain or heat-killed encapsulated strains yielded heterologous protection (31,32). Others (3,10,11,13) showed that noncapsular structures could induce immunity against several pneumococcal types. Au and Eisenstein demonstrated non-type-specific protection induced with subcellular fractions prepared from unencapsulated pneumococci which was not type specific (1).…”
mentioning
confidence: 99%